Donor‐derived M2 macrophages attenuate GVHD after allogeneic hematopoietic stem cell transplantation. Issue 4 (19th August 2021) - Hanaki, Ryo; Toyoda, Hidemi; Iwamoto, Shotaro; Morimoto, Mari; Nakato, Daisuke; Ito, Takahiro; Niwa, Kaori; Amano, Keishiro; Hashizume, Ryotaro; Tawara, Isao; Hirayama, Masahiro
Abstract: Introduction: Graft‐versus‐host disease (GVHD) is frequent and fatal complication following allogeneic hematopoietic stem cell transplantation (HSCT) and characteristically involves skin, gut, and liver. Macrophages promote tissue regeneration and mediate immunomodulation. Macrophages are divided into two different phenotypes, classically activated M1 (pro‐inflammatory or immune‐reactive macrophages) and alternatively activated M2 (anti‐inflammatory or immune‐suppressive macrophages). The anti‐inflammatory effect of M2 macrophage led us to test its effect in the pathophysiology of GVHD. Methods: GVHD was induced in lethally irradiated BALB/c mice. M2 macrophages derived from donor bone marrow (BM) were administered intravenously, while controls received donor BM‐mononuclear cells and splenocytes. Animals were monitored for clinical GVHD and analyzed. Results: We confirmed that administering donor BM‐derived M2 macrophages attenuated GVHD severity and prolonged survival after HSCT. Moreover, donor BM‐derived M2 macrophages significantly suppressed donor T cell proliferation by cell‐to‐cell contact in vitro. Conclusions: We showed the protective effects of donor‐derived M2 macrophages on GVHD and improved survival in a model of HSCT. Our data suggest that donor‐derived M2 macrophages offer the potential for cell‐based therapy to treat GVHD. Abstract : Adoptive transferred M2 macrophages prolong the survival of GVHD mice.